(untitled) (KULT_online, 2023)
In Domesticity on Display: Romanian Middle-Class Material Culture from Late Socialism to Today, Maria Christache analyzes the production of decorative objects as well as their use in the domestic sphere in the time period between socialism and postsocialism in Romenia. Her analysis of the role of material culture within such an eventful historical period acknowledges the centrality of objects in social relations and the potential of gifts to provide their givers and receivers with means of identification.